Left atrium function and deformation in very preterm infants with and without volume load. Issue 11 (17th September 2018) - de Waal, Koert; Phad, Nilkant; Boyle, Andrew
Abstract : Background: Left atrium (LA) function can be assessed by volumetric measurements, conventional and tissue Doppler, and more recently, deformation imaging using two‐dimensional speckle tracking echocardiography (2DSTE). 2DSTE allows for measurement of volume and deformation and can quantify the contribution of the reservoir, conduit, and contraction phase. A common cause for LA dysfunction in very preterm infants is volume overload with a patent ductus arteriosus (PDA). The aim of this study was to explore the feasibility and reliability of LA 2DSTE in preterm infants, and describe LA function with and without PDA volume load. Methods: We prospectively recruited preterm infants <30 weeks of gestation referred for assessment of a possible PDA. A cardiac ultrasound was performed at day 3 and in week 4 of life and analyzed using conventional techniques and 2DSTE. Results: Forty‐eight infants (32 with PDA) were included. LA 2DSTE analysis was feasible in 96% of measurements with good reliability of strain and volume parameters. Strain rate was less reliable. Poorer LA contraction and reservoir function was associated with larger LA volume index, higher inflow over the mitral valve at early diastole, higher EA ratio, and higher Ee' ratio. Poorer conduit function was associated with higher Ee' ratio. A larger PDA diameter was found to be an independent contributor to deteriorating LA contraction and reservoir function. Conclusion: LA 2DSTE analysis is feasible in preterm infants and provides detailed information on atrium mechanics. Further studies are needed to explore the clinical value of these new parameters in this population.